PENGARUH PEMANFAATAN MEDIA PEMBELAJARAN DARING TERHADAP SIKAP DIGITAL CITIZENSHIP PESERTA DIDIK PADA MATA PELAJARAN PPKN - amallia noviani; Muhammad Mona Adha; Rohman Rohma (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2022)
The country of Indonesia is currently undergoing rapid changes, namely the Covid-19 virus. The changes that occur are certainly very influential on the order of life, especially technology among the world of education. The educational environment has changed, where previously the learning process was carried out face-to-face, but now uses online learning media. Schools are one of the main factors in shaping the character of students, so that they can support the good use of technology, which is called digital citizenship. But in reality today, the reason is partly the lack of bad attitudes in the use of technology by students. The problem that will be discussed in this study is how the influence of online learning media in strengthening the Digital Citizenship attitude of students in Civics subjects. The research method used is a descriptive method with a quantitative approach. The data collection technique used the main technique, namely a questionnaire. The data analysis tool in this study uses SPSS version 20. Based on the results of the research conducted, it shows that there is an influence of online learning media in strengthening students' digital citizenship attitudes in Civics subjects with a large percentage of the effect, which is 56,5%. Keywords: Online Learning Media, Digital Citizenship, and Students